TEMPERATURE INDEX MELT MODELLING IN MOUNTAIN AREAS - Hock R. (My University, 2003)
Temperature index or degree-day models rest upon a claimed relationship between snow or ice melt and air temperature usually expressed in the form of positive temperatures. Since air temperature generally is the most readily available data, such models have been the most widely used method of ice and snow melt computations for many purposes, such as hydrological modelling, ice dynamic modelling or climate sensitivity studies. Despite their simplicity, temperature-index models have proven to be powerful tools for melt modelling, often on a catchment scale outperforming energy balance models. However, two shortcomings are evident: (1) although working well over long time periods their accuracy decreases with increasing temporal resolution; (2) spatial variability cannot be modelled accurately as melt rates may vary substantially due to topographic effects such as shading, slope and aspect angles. These effects are particularly crucial in mountain areas. This paper provides an overview of temperature-index methods, including glacier environments, and discusses recent advances on distributed approaches attempting to account for topographic effects in complex terrain, while retaining scarcity of data input. In the light of an increasing demand for melt estimates with high spatial and temporal resolution, such approaches need further refinement and development.
Keywords: TEMPERATURE INDEX MODELS; DEGREE-DAY FACTOR; MELT MODELLING; GLACIER MASS BALANCE